The Implementation of Empowerment Program for Indonesian Ex-Migrant Workers to Improve Their Welfare - Rani Kumala Sari; Sjamsiar Sjamsuddin; Suryadi Suryadi (Sekolah Pascasarjana Universitas Brawijaya, 2021)
The government through the Department of Manpower and Transmigration issued an empowerment program for ex-migrant workers. The program was implemented by The Department of Manpower and Transmigration of Tulungagung Regency based on PERKA BNP2TKI Nomor 04 tahun 2017 related to the empowerment of Indonesian migrant workers. There were 3,867 migrant workers from Tulungagung Regency in the year 2017. The empowerment program focused on the establishment of productive and entrepreneurial businesses, but still considered the potential of each region.The implementation of the empowerment program was still focused on two desmigrative villages in Tulungagung Regency, namely Betak Kalidawir and Mirigambar Sumbergempol, with the majority of the populations work as migrant workers. The background of the empowerment program for ex-migrant workers is the condition that ex-migrant workers in Tulungagung when returning to their regions didn’t have jobs and triggered to return to work abroad again. The purpose that the skills and capital by ex-migrant workers can be used effectively and maximally. So that when returning to the area, ex-migrant workers have jobs and open jobs. In this study, the authors used a qualitative research method with a descriptive approach. The data were collected through interviews, observation, and documentation for further analyzed by using interactive analysis model Miles, Huberman and Saldana (2014). The findings obtained are that the implementation of the program has not been running optimally. The findings obtained that the implementation hasn’t run optimally, especially with several strategies and requirements set by the organization that haven’t been carried out maximum.